At-risk individual's perspectives of Spinocerebellar Ataxia (SCA) Presymptomatic Testing (PT) - Lloyd, Deanah (Department of Pathology, 2022)
Since the introduction of presymptomatic testing for Spinocerebellar Ataxia in South Africa, no research has looked at the impact, perceptions or acceptance of such testing within this diverse population. Despite the relatively high frequencies of late onset autosomal dominant conditions in South Africa, the uptake of presymptomatic testing by those at-risk of inheriting these conditions has been lower than that seen internationally. This research project sought to understand these low levels of utilisation, by exploring the perceptions of those at-risk of inheriting Spinocerebellar Ataxia towards presymptomatic testing. In depth semi-structured interviews were conducted with six individuals at-risk of inheriting Spinocerebellar Ataxia. The interviews were transcribed verbatim and thematically analysed. The four themes that emerged from the data included: 1) Caregiving, 2) Relationships, 3) Being At-Risk and 4) Presymptomatic Testing (PT) Perceptions. These themes explore the significant and long-lasting burdens faced both physically and emotionally by the affected individual as well as their relatives. With no currently available way of preventing or curing the condition, those atrisk described being left with a sense of hopelessness and anxiety about their future. The at-risk individuals' perceptions and fears were often linked to their and their family's experiences of the condition. Additionally, their perceptions of presymptomatic testing, although positive, did not correlate with testing utilisation amongst the participants. As such, the current underutilisation of presymptomatic testing in South Africa was found to be due to the at-risk individuals' fears of the result and its' perceived consequences, rather than a negative perception of presymptomatic testing. This is significant as it indicates that the current lack of uptake of presymptomatic testing is due to external factors unrelated to the test itself. As such, genetic counsellors should focus their efforts on counselling the individual through their fears as opposed to primarily offering presymptomatic testing. Although these findings contribute to our understanding of this previous understudied population, they cannot be extrapolated to apply to the entire South African at-risk population due to the small sample size of the study. This knowledge however, may assist in improving the presymptomatic testing process by providing greater insight into the population's experiences and perspectives. Thus, it is recommended that future studies explore ways that genetic counselling sessions and the presymptomatic testing process could be altered to incorporate this knowledge.